DISC1 Regulates Primary Cilia That Display Specific Dopamine Receptors - Marley, Aaron; von Zastrow, Mark (PLOS ONE, 2010)
Background Mutations in the DISC1 gene are strongly associated with major psychiatric syndromes such as schizophrenia. DISC1 encodes a cytoplasmic protein with many potential interaction partners, but its cellular functions remain poorly understood. We identified a role of DISC1 in the cell biology of primary cilia that display disease-relevant dopamine receptors. Methodology/Principal Findings A GFP-tagged DISC1 construct expressed in NIH3T3 cells and rat striatal neurons localized near the base of primary cilia. RNAi-mediated knockdown of endogenous DISC1 resulted in a marked reduction in the number of cells expressing a primary cilium. FLAG-tagged versions of the cloned human D1, D2 and D5 dopamine receptors concentrated highly on the ciliary surface, and this reflects a specific targeting mechanism specific because D3 and D4 receptors localized to the plasma membrane but were not concentrated on cilia. Conclusions/Significance These results identify a role of DISC1 in regulating the formation and/or maintenance of primary cilia, and establish subtype-specific targeting of dopamine receptors to the ciliary surface. Our findings provide new insight to receptor cell biology and suggest a relationship between DISC1 and neural dopamine signaling.